KOMPETENSI PERADILAN TATA USAHA NEGARA BERDASARKAN UNDANGUNDANG TENTANG ADMINISTRASI PEMERINTAHAN - Dian Utami Mas Bakar; Audyna Mayasari Muin (The Juris, 2018)
The existence of the Administrative Court becomes a necessity in a legal sta- te in order to ensure that the Decision and/or the Acts of the Agency and/or Government Officials on Citizens can not be conducted arbitrarily. The en- actment of Government Administration Act implies the competence of Admi- nistrative Courts. Some of the arrangements governing the competence of the Administrative Court are not done through the amendment of Adminis- tration Courts Act itself but through the Administration of Government Act, so that in this Act contains provisions of competence changes and even addi- tional competence of the Administrative Court.